2021
DOI: 10.1155/2021/6642734
|View full text |Cite
|
Sign up to set email alerts
|

A Detailed Numerical Study of NOx Kinetics in Counterflow Methane Diffusion Flames: Effects of Fuel-Side versus Oxidizer-Side Dilution

Abstract: Dilution combustion has been widely utilized due to various merits, such as enhanced efficiency, fewer pollutants emissions, and even a promising future in alleviating global warming. Diluents can be introduced through the oxidizer or fuel side to achieve the desired combustion properties, and H2O and CO2 are the most common ones. A comprehensive comparison between the different dilution methods still lacks understanding and optimizes the dilution combustion technologies. This study numerically compared the ef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 30 publications
0
3
0
Order By: Relevance
“…The present study is a follow-up to our previous work, ref, where we investigated the influence of fuel-side versus oxidizer-side dilutions on NO emissions in CH 4 counterflow diffusion flames. Expanding on this basis, the objectives of this study are 2-fold: (1) to compare the effects of fuel-side versus oxidizer-side dilution on the general characteristics of a more application-relevant multidimensional flame and (2) to illustrate how dilution strategy alters the detailed flame structure and general flame height of a laminar coflow CH 4 diffusion flame from the perspectives of heat transfer, molecular diffusion, and chemical kinetics.…”
Section: Introductionmentioning
confidence: 93%
“…The present study is a follow-up to our previous work, ref, where we investigated the influence of fuel-side versus oxidizer-side dilutions on NO emissions in CH 4 counterflow diffusion flames. Expanding on this basis, the objectives of this study are 2-fold: (1) to compare the effects of fuel-side versus oxidizer-side dilution on the general characteristics of a more application-relevant multidimensional flame and (2) to illustrate how dilution strategy alters the detailed flame structure and general flame height of a laminar coflow CH 4 diffusion flame from the perspectives of heat transfer, molecular diffusion, and chemical kinetics.…”
Section: Introductionmentioning
confidence: 93%
“…The most comprehensive detailed mechanism for combustion of CH 4 -CO-H 2 mixture is known as GRI 3.0 (Gas Research Institute) originally designed by researchers at combustion laboratory of University of California, Berkeley [23]. The mechanism contains 55 species and 325 reaction which have been incorporated in CFD models to study CO-H 2 mixture (without CH 4 content) [24,25] and NOx formation [26][27][28][29][30][31]. To enhance the simulation speed, most of the researchers have used reduced GRI mechanisms where some species and therefore reactions are eliminated depending on the specific reactive flow conditions [32][33][34][35][36].…”
Section: Introductionmentioning
confidence: 99%
“…In their study, the chemical kinetics employed is GRI-Mech 3.0, which includes 53 species and 325 elementary reactions, and it has been developed for gas phase natural reactions and includes hydrocarbon species up to C 3 and the problem with natural gas; it is hard to autoignite and therefore requires a higher compression ratio, some amount of intake heating, or some type of preignition. Huanhuan et al [12] conducted a theoretical study on the effects of H 2 O and CO 2 dilution in the oxidizer or fuel stream on counterflow methane diffusion flames, emphasizing NO formation kinetics. eir results showed that the impact of different radiation heat transfer models on NO emissions diminishes with increase in the dilution ratio.…”
Section: Introductionmentioning
confidence: 99%